DELIVERING ENGLISH CLASS THROUGH YOUTUBE TO THE FIRST SEMESTER STUDENTS OF ISLAMIC EDUCATION MANAGEMENT STUDY PROGRAM AT DATOKARAMA STATE ISLAMIC UNIVERSITY PALU - Afifah Afifah; Suleman Suleman (Guru Tua : Jurnal Pendidikan dan Pembelajaran, 2022)
Social media platform has become one of the main attributes for teaching and learning. One of those digital platforms widely used is YouTube. YouTube functions not only as a social media for interacting with the world, but also as a teaching media for delivering material. This research is conducted to gain more information related to the use of YouTube in teaching and learning. The research question was, “How was the use of YouTube in delivering English class to the first semester students of Islamic Education Management Study Program at Datokarama State Islamic University Palu?” This is a case study in qualitative research. The instruments applied in this research were observation which was conducted as many as six meetings and an interview with eight questions to thirteen first semester students of Islamic Education Management Study Program at Datokarama State Islamic University Palu. The result of this research showed the point of view from the lecturers and the students related to the research question. The lecturers viewed YouTube as one of solutions for solving the problem of delivering distance learning. Explaining material of English via YouTube can be seriously challenging. The lecturers should perform well in front of the camera while delivering the material. From the students’ point of view, YouTube helped them understand the explanation of English material easily. They did not have to download videos and save them in the phone memory. They only needed to click the link and watch the videos in YouTube.